2017
DOI: 10.1039/c7ra08092a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies on corrosion inhibition of 4-amidinophenyl-2,2′-bifuran and its analogues in acidic media

Abstract: Corrosion inhibition studies of carbon steel (CS) in 1 M HCl by newly synthesized bichalcophene compounds namely; 4-(2,2′-bifuran-5-yl)benzamidine (MA-0947) and 6-(2,2′-bifuran-5-yl)nicotinamidine (MA-0941) and 6-[5-(thiophen-2-yl)furan-2-yl]nicotinamidine (MA-0940).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…In addition, it's essential to deduce the presence of C, O and Cu peaks in the EDX graphs of the copper surface matching to the sample inundated for 12 h. In solutions involving the favorable concentration of the ionic liquids, the creation of a thin protective lm of ILs is matching with the SEM micrographs. 49 3.6.2 Atomic force microscopy (AFM). Further morphological evaluation of the copper surface was applied via AFM in the presence and absence of the ILs with concentrations (0.05 mM) aer inundation 12 h. The AFM micrographs were shown in Fig.…”
Section: Surface Analysismentioning
confidence: 99%
“…In addition, it's essential to deduce the presence of C, O and Cu peaks in the EDX graphs of the copper surface matching to the sample inundated for 12 h. In solutions involving the favorable concentration of the ionic liquids, the creation of a thin protective lm of ILs is matching with the SEM micrographs. 49 3.6.2 Atomic force microscopy (AFM). Further morphological evaluation of the copper surface was applied via AFM in the presence and absence of the ILs with concentrations (0.05 mM) aer inundation 12 h. The AFM micrographs were shown in Fig.…”
Section: Surface Analysismentioning
confidence: 99%
“…Mild steel has a wide range of applications in production and life because of its excellent properties. [1][2][3][4][5] These include the production of various building components, containers, tanks, furnaces and agricultural machinery, in addition to various heat exchange equipment, heat transfer equipment and cooling equipment, etc. However, thermal equipment such as boilers and heat exchangers gradually form various types of dirt during use, and the poor thermal conductivity of this dirt causes the local temperature of the furnace tubes to rise, which reduces the strength of steel materials and oen causes tube explosion accidents as well as affecting the boiler operation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have indicated that the DNP basis set is of comparable quality to the 6-31G Gaussian basis set and it is more accurate than the Gaussian basis set of the same size. [46][47][48][49] The integration accuracy and the self-consistent eld tolerance were both set as ne. Core treatment was used to all electrons.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%